Comparative assessment of bone collagen recovered from different livestock and poultry species: microstructure, physicochemical characteristics and functional properties. (18th June 2022) - Liu, Hong; Guo, Yujie; Xu, Xiong; Liu, Jiqian; Zhang, Hongru; Qi, Liwei; Zhang, Chunhui; Gao, Hongwei
Summary: This study aimed to recover and characterise livestock and poultry bone collagens (LBCs) from yak (YBC), bovine (BBC), porcine (PBC) and chicken (CBC) sources and perform comparative assessment on their microstructure, physicochemical and functional properties. Amino acid compositions, SDS–PAGE and spectroscopic analysis confirmed that LBCs were intact triple‐helical collagen I of [α1(I)]2α2(I) with some structural differences. Scanning electron microscope (SEM) results showed that LBCs displayed a loose and porous fibrous meshwork. The Td values of SCI, YBC, BBC, PBC and CBC were 42.6, 42.3, 44.6, 41.9 and 42.9 °C, and 5.81, 7.15, 6.28, 6.79 and 5.33 of pI values, respectively. Structural differences also endowed LBCs with dissimilar functional properties, such as water‐holding capacity, foaming and emulsifying. The structure–function correlations analysis revealed the structure–function correlations of LBCs. This study offered a new prospect that the sustainable livestock and poultry bones (LBs) might be valorised as an alternative collagen source and provided useful information for the industrial production and fostered further rational valorisation of LBCs. Abstract : Livestock and poultry bone collagens (LBCs) were recovered from yak (YBC), bovine (BBC), porcine (PBC) and chicken (CBC) bone byproducts. Comparative assessment and structure‐function correlation analysis on microstructure, physicochemical, functional properties of LBCs were performed to offer a new prospect that the sustainable livestock and poultry bone byproducts might be valorized as an alternative collagen source, and provided useful information for the industrial production and fostered the further rational valorization of LBCs.